Was Ibn Kathīr the 'Spokesperson' for Ibn Taymiyya? Jonah as a Prophet of Obedience. Issue 1 (February 2014) - Mirza, Younus Y.
<x xml:space="preserve">Abstract</x> Current scholarship views the Qur'anic exegesis of Ibn Kathīr as the product of the great Ibn Taymiyya. This paper argues that Ibn Kathīr had a distinct Qur'anic hermeneutic and exegesis to that of Ibn Taymiyya. While Ibn Taymiyya's engagements with the Qur'an were tied to theological refutations, Ibn Kathīr's exegesis is primarily a ḥadīth evaluation (takhrīj) which assessed the tradition-based exegesis that pre-dated him. Ibn Kathīr carefully sorts through the exegeses of al-Ṭabarī and Ibn Abī Ḥātim al-Rāzī to find authentic traditions that fit with his moral and ethical values. His exegesis further takes positions that are contrary to Ibn Taymiyya's. For instance, on the issue of the infallibility (ʿiṣma) of the prophets, Ibn Taymiyya argues that prophets sinned but did not persist in sin. Ibn Kathīr, in contrast, maintained that prophets were constantly aided by God and does not highlight their mistakes. Their different definitions are seen in their contrasting accounts of the Prophet Jonah: Ibn Taymiyya viewed Jonah's release from the whale as part of his repentance, while Ibn Kathīr saw it as part of his previous obedience.